Elastic properties of electrospun PVDF nanofibrous membranes: Experimental investigation and numerical modelling using pixel-based finite element method - Sukiman, Muhamad Shafiq; Andriyana, Andri; Ang, Bee Chin; Metselaar, Hendrik Simon Cornelis (Elsevier, 2020)
In this paper, experimental investigation and numerical modelling of the mechanical properties of polyvinylidene fluoride (PVDF) nanofibrous membranes produced by electrospinning are addressed. Membranes with three different diameters are fabricated by adjusting the needle-collector distance during electrospinning. The fiber morphology and the physical properties of the resulting membranes are investigated using Scanning Electron Microscopy (SEM) while their elastic properties are probed using conventional tensile tests. It is found that the membrane with the largest nanofiber diameters are filled with large beads while the contrary is found in the membrane with the smallest nanofiber diameter. Consequently, the membrane with the smallest nanofiber diameter yielded the highest membrane Young's modulus thanks to better fiber packing and higher crystallinity in the nanofibers. Next, the experimental results serve as basis for a pixel-based finite element method (FEM) which is applied directly on the SEM images of the membranes. This technique has the advantage of providing estimations of mechanical properties from the real structure of the membranes. Two parameters are needed for this linear elastic analysis: the elastic modulus of a single fiber and the fiber percentage in the membrane. Results show that the model predictions are in good agreement with experimental data. These results suggest that the pixel-based FEM could be a promising nondestructive alternative to the conventional tensile tests. © 2019 Elsevier Ltd